Evaluación de factores psicológicos asociados al uso de la bicicleta en estudiantes de la Universidad de los Andes (2017)
The purpose of this study is to contribute to the growing body of knowledge that seeks to engage the behavioral sciences with the needs of our society in terms of sustainable transport. This research is focused on the identification of the psychological factors associated with the use of the bicycle in the students of the University of the Andes.--Tomado del Formato de Documento de Grado.